Emergence of Progressive Mutations in SARS-CoV-2 From a Hematologic Patient With Prolonged Viral Replication - Garcia-Vidal, Carolina; Iglesias-Caballero, María; Puerta-Alcalde, Pedro; Mas, Vicente; Cuesta-Chasco, Genoveva; Garcia-Pouton, Nicole; Varona, Sarai; Pozo, Francisco; Vázquez-Morón, Sonia; Marcos, Maria Angeles; Soriano, Alex; Casas, Inmaculada; et al. (Frontiers in Microbiology, 2022)
We documented a hematologic patient with prolonged SARS-CoV-2 viral replication in whom emergence of viral mutations was documented after the consecutive use of antivirals and convalescent plasma. The virus detected in the last of twelve clinical samples (day 237) had accumulated 22 changes in amino acids and 29 in nucleotides. Some of these changes, such as the E484Q, were mutations of concern as defined by WHO. This finding represents an enormous epidemiological threat and poses a major clinical challenge. Combined antiviral strategies, as well as specific strategies related to the diagnostic approach of prolonged infections for this specific population, may be needed.